Unconscious Unease and Self-Handicapping: Behavioral Consequences of Individual Differences in Implicit and Explicit Self-Esteem - Spalding, Leah R.; Hardin, Curtis D. (Psychological Science, 1999)
In contrast to measures of explicit self-esteem, which assess introspectively accessible self-evaluations, measures of implicit self-esteem assess the valence of unconscious, introspectively inaccessible associations to the self. This experiment is the first to document a relationship between individual differences in implicit self-esteem and social behavior: Participants completed either a self-relevant or a self-irrelevant interview, and were then rated by the interviewer on their anxiety. When the interview was self-relevant, apparent anxiety was greater for participants low in implicit self-esteem than for participants high in self-esteem; implicit self-esteem did not predict anxiety when the interview was self-irrelevant. Explicit self-esteem did not predict apparent anxiety in either interview, but did predict participants' explicit self-judgments of anxiety. Self-handicapping about interview performance was greater for participants low in both explicit and implicit self-esteem than for those high in these measures. The experiment provides direct evidence that effects of implicit and explicit self-esteem may be dissociated.